PENGEMBANGAN KARAKTER WIRAUSAHA SISWA MELALUI PEMBELAJARAN KEWIRAUSAHAAN DI SEKOLAH MENENGAH KEJURUAN - CUCU SUTIANAH, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Vocational high school or commonly referred to as SMK is one of the formal education institutions in the vocational field in Indonesia that produces prospective workers who are ready to work and face the industrial world. The number of SMKs in Indonesia is inversely proportional to the high unemployment rate and the entrepreneur index in Indonesia is still below 2% or below the minimum number it should be. Learning at SMK should have a goal in developing entrepreneurial character. Through a descriptive survey research method with data collection techniques of documentation study, interviews, literature study and observation at national reference schools namely SMKN 9 Bandung, SMKN 2 Bale Endah and SMKN 3 Garut to related teachers and students of the study package of fashion design. which fosters entrepreneurial character. The learning process includes a) planning; b) implementation and c) evaluation describes the objectives and research results. The results showed that overall the implementation of learning in developing entrepreneurial character in the research location has been carried out quite well, but still requires development on the achievement of competency indicators in accordance with the learning objectives.